Computational methods for large systems : electronic structure approaches for biotechnology and nanotechnology - Reimers, Jeffrey R.; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
'While its results normally complement the information obtained by chemical experiments, computer computations can in some cases predict unobserved chemical phenomena Electronic-Structure Computational Methods for Large Systems gives readers a simple description of modern electronic-structure techniques. It shows what techniques are pertinent for particular problems in biotechnology and nanotechnology and provides a balanced treatment of topics that teach strengths and weaknesses, appropriate and inappropriate methods. It's a book that will enhance the your calculating confidence and improve your ability to predict new effects and solve new problems.'--
'Provides a simple description of modern electronic-structure techniques. Shows what techniques are pertinent for particular problems in biotechnology and nanotechnology. Provides a balanced treatment of the topics that teaches strengths and weaknesses, appropriate and inappropriate methods. Provides confidence to calculators that their results are useful for predicting new effects and for interpreting newly presented problem scenarios - reference tool for industrial scientists who develop applications as well as a teaching aid for new graduate students in computational chemistry, physics, biochemistry, biotechnology, materials science and nanoscience'--
Frontmatter -- DFT: The Basic Workhorse. Principles of Density Functional Theory: Equilibrium and Nonequilibrium Applications / Ferdinand Evers -- SIESTA: A Linear-Scaling Method for Density Functional Calculations / Julian D Gale -- Large-Scale Plane-Wave-Based Density Functional Theory: Formalism, Parallelization, and Applications / Eric Bylaska, Kiril Tsemekhman, Niranjan Govind, Marat Valiev -- Higher-Accuracy Methods. Quantum Monte Carlo, Or, Solving the Many-Particle Schr̲dinger Equation Accurately While Retaining Favorable Scaling with System Size / Michael D Towler -- Coupled-Cluster Calculations for Large Molecular and Extended Systems / Karol Kowalski, Jeff R Hammond, Wibe A de Jong, Peng-Dong Fan, Marat Valiev, Dunyou Wang, Niranjan Govind -- Strongly Correlated Electrons: Renormalized Band Structure Theory and Quantum Chemical Methods / Liviu Hozoi, Peter Fulde -- More-Economical Methods. The Energy-Based Fragmentation Approach for Ab Initio Calculations of Large Systems / Wei Li, Weijie Hua, Tao Fang, Shuhua Li -- MNDO-Like Semiempirical Molecular Orbital Theory and Its Application to Large Systems / Timothy Clark, James J P Stewart -- Self-Consistent-Charge Density Functional Tight-Binding Method: An Efficient Approximation of Density Functional Theory / Marcus Elstner, Michael Gaus -- Introduction to Effective Low-Energy Hamiltonians in Condensed Matter Physics and Chemistry / Ben J Powell -- Advanced Applications. SIESTA: Properties and Applications / Michael J Ford -- Modeling Photobiology Using Quantum Mechanics and Quantum Mechanics/Molecular Mechanics Calculations / Xin Li, Lung Wa Chung, Keiji Morokuma -- Computational Methods for Modeling Free-Radical Polymerization / Michelle L Coote, Ching Y Lin -- Evaluation of Nonlinear Optical Properties of Large Conjugated Molecular Systems by Long-Range-Corrected Density Functional Theory / Hideo Sekino, Akihide Miyazaki, Jong-Won Song, Kimihiko Hirao -- Calculating the Raman and HyperRaman Spectra of Large Molecules and Molecules Interacting with Nanoparticles / Nicholas Valley, Lasse Jensen, Jochen Autschbach, George C Schatz -- Metal Surfaces and Interfaces: Properties from Density Functional Theory / Irene Yarovsky, Michelle J S Spencer, Ian K Snook -- Surface Chemistry and Catalysis from Ab InitioBased Multiscale Approaches / Catherine Stampfl, Simone Piccinin -- Molecular Spintronics / Woo Youn Kim, Kwang S Kim -- Calculating Molecular Conductance / Gemma C Solomon, Mark A Ratner -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Nanostructured materials -- Computer simulation; Nanotechnology -- Data processing; Biotechnology -- Data processing; Electronics -- Materials -- Computer simulation; SCIENCE -- Nanoscience; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Electronic books